Manual patient transfers: factors that influence decisions and kinematic strategies employed by nursing aides. Issue 4 (3rd April 2019) - Lafleur, Benoit; Weaver, Tyler B.; Tondat, Alyssa; Boscart, Veronique; Laing, Andrew C.
Abstract: While extensive literature has characterised factors that influence the acceptable mass of 'boxes' during MMH tasks, less is known about these factors when moving 'people' in healthcare settings. This study examined factors that influence decisions/approaches employed during manual patient transfers. Sixteen nursing aides manually-transferred a standardised 'patient'; patient mass was adjusted (using a weight vest) to determine a maximum acceptable patient mass for this task ( massmax ). Grip strength was the only worker characteristic significantly associated with massmax ( r  = 0.48). Older worker age was associated with smaller peak trunk flexion ( r  =  −0.58) and shoulder abduction ( r  =  −0.59), and greater trunk axial twist ( r  = 0.52). Workers emphasised that patient characteristics (e.g. physical/cognitive status) influenced their decisions when performing transfers. These findings extend previous literature by suggesting that grip strength is a useful predictor of perceived work capacity, older workers adapt protective postural strategies during patient transfers and worker-patient dynamics are crucial during this high-risk occupational task. Practitioner Summary: This study examined manual patient transfers performed by nursing aides. Worker grip strength (but not age or size) was associated with perceptions of maximum acceptable patient mass. Kinematic changes suggested more conservative strategies used by older workers. Workers emphasised that patient characteristics substantially influenced their decisions when performing transfer tasks.